(untitled) (Western European Journal of Historical Events and Social Science, 2025)
The article describes the end of the 16th century and the beginning of the 17th century, which was marked as a new period in the development of the Naqshbandi order when the branch of the tariqah Naqshbandi-Mujaddidi emerged. Moreover, it has investigated the specific role of Ahmad Sirhindi Farooqi Rabbani (1564-1624), who lived in Sirhind, India in the late 16th and early 17th centuries, who was one of the theorists of the order and whose name is mentioned in a series of orders that are currently in use in our country.